2015
DOI: 10.1002/pd.4556
|View full text |Cite
|
Sign up to set email alerts
|

Safe and effective cryopreservation methods for long‐term storage of human‐amniotic‐fluid‐derived stem cells

Abstract: We identified three suitable cryopreservation protocols because of high cell recovery and unchanged SC characteristics. Given one of these, the slow-freezing solution, is compatible with current good manufacturing practice legislation, it may be ultimately clinically used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…In our study, the 10% (v/v) DMSO concentration of associated with 20% FBS demonstrated to be effective for the cryopreservation of UCIM-MSCs. These results are in accordance with the concentration used in other studies (Hennes et al, 2015;Kim et al, 2015;Mun evar et al, 2015;Duan and Lopez, 2016;Ercolin et al, 2016;Irioda et al, 2016).…”
Section: Figuresupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, the 10% (v/v) DMSO concentration of associated with 20% FBS demonstrated to be effective for the cryopreservation of UCIM-MSCs. These results are in accordance with the concentration used in other studies (Hennes et al, 2015;Kim et al, 2015;Mun evar et al, 2015;Duan and Lopez, 2016;Ercolin et al, 2016;Irioda et al, 2016).…”
Section: Figuresupporting
confidence: 92%
“…Although it has disadvantages mainly related to immunogenicity for clinical application purposes, FBS has an important role in the cryopreservation process by stabilizing cell membranes, protecting cells from free radicals and adjusting osmotic pressure (Marquez‐Curtis et al, ). Many studies, used FBS for cultivation (Barberini et al, ; Maia et al, ; Chang et al, ; Tang et al, ) and cryopreservation (Mambell et al, ; Martinello et al, ; Hennes et al, ; Kim et al, ; Munévar et al, ; Duan and Lopez, ; Ercolin et al, ; Irioda et al, ) possibly by its positive aspect in cell growth and benefits during freezing. However, it is important to point that for therapeutic purposes, the FBS must be washed out before cell transfer (Maia et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, protein expression in the cell types found in AFMSCs does not affect the differentiation capacity of AFMSC preparations (PMID: 25608581), and the ectopic expression of Oct-4 in hAFMSCs could be an alternative method to produce pluripotency [12], while the selective expression of SOX9 and induction of Wnt signaling can be used to specifically differentiate cells to neurons and promote neurogenesis, respectively [13,14]. However, before these methodologies can be used, it is important to identify a suitable cryopreservation protocol, such as the slow-freezing solution [15]. In a recent study, Zong et al has shown to direct AFSCs to differentiate into neurons with characteristics of functionality using inner stem cells derived as a feeder layer [16].…”
Section: Stemness Of Cells Derived From the Amniotic Fluidmentioning
confidence: 99%
“…Notwithstanding, these stemness characteristics of AFSCs do not inhibit the differentiation capacity of AFMSC preparation, although the ectopic expression of Oct-4 in hAFMSCs could be a secondary factor in achieving pluripotency [12], while the selective expression of SOX9 and introduction of Wnt signaling can be used to explicitly differentiate cells into neurons and promote neurogenesis [13,14]. However, before these procedures can be initiated, an appropriate cyropreservative protocol must be identified, such as a slow freezing solution [15]. In their recent study, Zong et al not only found the ability of AFSCs to differentiate into functional neurons using inner stem cells as a feeder layer, but also identified the Wnt signaling pathway as an integral aspect of initiating neurogenesis [16].…”
Section: Stemness Of Cells Derived From the Amniotic Fluidmentioning
confidence: 99%